2014
DOI: 10.2478/prolas-2014-0016
|View full text |Cite
|
Sign up to set email alerts
|

Anther Culture Effectiveness in Producing Doubled Haploids of Cereals/ Putekðòu Kultûras Efektivitâte Graudaugu Dubultoto Haploîdu Izveidoðanâ

Abstract: Our goal was to improve the method of obtaining double haploids (DH) by anther culture from Latvian breeding material for several agriculturally important cereals in Latvia: barley, spring and winter wheat. Hybrids from Latvian breeders were initial material. It was found that copper (2.5 mg/l) added to barley anther pre-treatment media and to both barley (C3) and wheat (liquid AMC) induction media, resulted in a higher percentage of green plants-regenerants. In general, the winter wheat hybrids exhibited lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…Furthermore, some research reported values higher than 100 green plantlets/100 anthers such as; (BROUGHTON, 2011;LANTOS et al, 2013;CASTILLO et al, 2015). In this investigation, the overall mean was 9.76 green plantlets/100 anthers, which exceeded the means of green plantlets in previously published winter wheat breeding programs (HOLME et al, 1999;TUVESSON et al, 2000;KONDIC-SPIKA et al, 2008;EL-HENNAWY et al, 2011;LANTOS et al, 2013;GRAUDA et al, 2014), where the means ranged between 0.4 and 5.8 green plantlets/100 anthers.…”
Section: Percentage Of Acclimatized Plantlets Among Ac-derived Transplanted Plantletscontrasting
confidence: 49%
“…Furthermore, some research reported values higher than 100 green plantlets/100 anthers such as; (BROUGHTON, 2011;LANTOS et al, 2013;CASTILLO et al, 2015). In this investigation, the overall mean was 9.76 green plantlets/100 anthers, which exceeded the means of green plantlets in previously published winter wheat breeding programs (HOLME et al, 1999;TUVESSON et al, 2000;KONDIC-SPIKA et al, 2008;EL-HENNAWY et al, 2011;LANTOS et al, 2013;GRAUDA et al, 2014), where the means ranged between 0.4 and 5.8 green plantlets/100 anthers.…”
Section: Percentage Of Acclimatized Plantlets Among Ac-derived Transplanted Plantletscontrasting
confidence: 49%
“…DH generation techniques have been of great value to breeders, by speeding up cultivar development (Forster et al 2007;Germanà 2011) as well as to researchers by creating ideal material for transformation or genetic mapping (Kumlehn et al 2006;Poland et al 2012). The usefulness of androgenesis as the means of DHs production depends on reproducibility and efficiency, preferably independent of genetic constitution of the donor plants stocks (Ferrie and Caswell 2011;Grauda et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some findings recorded maximum values between 25-37 green plantlets/100 anthers (Trottier et al, 1993;Navarro-Alvarez et al, 1994;Lantos et al, 2013;Weigt et al, 2020). The total average of the production of green plantlets/100 anthers, which is between 0.40 and 9.76 green plantlets/100 anthers depending on the used protocol was recorded from previous winter wheat breeding programs by Masojc et al (1993); Holme et al (1999); Tuvesson et al (2000); Kondic-Spika et al (2008); El-Hennawy et al (2011); Grauda et al (2014); Weigt et al (2019Weigt et al ( , 2020; Kanbar et al (2020aKanbar et al ( , 2020b.…”
mentioning
confidence: 87%
“…Their results showed that the spring genotypes achieved a higher number of embryo-like structures and green plantlets. Grauda et al (2014) investigated the androgenetic induction of sixteen winter wheat hybrids and five spring hybrids by anther culture method. They asserted that the spring wheat hybrids produced higher embryogenesis than the winter wheat hybrids, but the winter wheat hybrids had higher green plantlet regeneration than the spring wheat hybrids.…”
mentioning
confidence: 99%